PENGARUH LINGKUNGAN KELUARGA TERHADAP PERILAKU BULLYING PESERTA DIDIK KELAS VII DI SMP NEGERI 16 PADANG - Mifthahhul Jannah; Suryadi; Joni Adison (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the influence of the family environment on the bullying behavior of seventh grade students at SMP Negeri 16 Padang. The background of this study is the high number of bullying cases in schools that can have a negative impact on the psychological and social development of students. This study uses a quantitative method with a simple linear regression approach. The sample consisted of 68 students selected through a total sampling technique. The instrument used was a questionnaire. The results of the study indicate that: (1) the students' family environment is in the low category, (2) bullying behavior is in the fairly high category, and (3) there is a significant influence between the family environment and bullying behavior by 15%. These results indicate the importance of the family's role in shaping students' social behavior.